An Ecofeminist Interpretation of Selected Nature Poems by Emily Dickinson - Mageed, Rania Mohamed Abdel (IJRDO - Journal of Social Science and Humanities Research, 2017)
As one of the most prominent women poets in the nineteenth century, Emily Dickinson (1830-1886) made a great impact in the field of American literature. Dickinson’s genius for creating poetry was incontrovertible. Her profound thoughts, creative images, unique writing style and innovation all established her high position as an important woman poet. Her nearly eighteen hundred poems have been increasingly attracting critics from all over the world to interpret and analyze Dickinson’s poetry from various perspectives applying psychology, linguistics, phenomenology and feminist literary criticism. Critics, however, seldom research on the combination of her ecological awareness and feminist consciousness. As a 19th century woman, long before the feminist movement and ecological activism, Dickinson expressed her rebellion to Male Supremacy Culture and showed her ecological awareness in her works. This paper applies the ecofeminist approach on selected nature poems by Emily Dickinson to scrutinize her claim upon ecology to challenge the established gender roles. The research further aims to provide a detailed ecofeminist interpretation and present a new perspective to appreciate the nature poetry written by Emily Dickinson.